FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG: STUDI KASUS PERHUTANAN SOSIAL, DESA KARANGBENDO - Seta, Kurangga; Zamrodah, Yuhanin; Budiman, Eko Wahyu; Prayudhi, Luhur Aditya (grafting, 2025)
This study aims to examine the characteristics of farmers and the influence of education, type of occupation, land area, and age on the income level of social forestry farmers in Karang Bendo Village, Ponggok District, Blitar Regency. The research method used is descriptive analysis and multiple linear regression analysis. The independent variables include education, occupation, land area, and age of farmers, while the dependent variable is the farmers' income. The study involved 25 respondents, with characteristics showing that most farmers had elementary school education, were primarily engaged in farming, were male, had an average land area of < 1000 m², and were aged between 40-50 years. The results of the multiple linear regression analysis indicate that only the land area variable significantly affects farmers' income, with a significance value of 0.002 (p < 0.05) and a t-value of 3.473 > t-table of 2.086.